Menyoroti Kebijakan Hukum Pidana terhadap Kasus Perdagangan Perempuan di Indonesia dengan Modus Rekrutmen melalui Media Sosial - Ronaldo William Limadibrata; Ahmad Jamaludin (Jurnal Hukum Lex Generalis, 2025)
In recent years, the trafficking of women, particularly young girls, has shown a significant increase, representing a humanitarian crisis that requires urgent attention. The rapid advancement of information technology has transformed recruitment methods, where strategies such as phishing, algorithmic manipulation, and false promises through social media have become dominant instruments. However, the Law on the Eradication of Human Trafficking Crimes (Law No. 21 of 2007) has yet to accommodate an operational definition of “digital fraud,” creating disharmony with the Personal Data Protection Law (Law No. 27 of 2022) and the Sexual Violence Crime Law (Law No. 12 of 2022). This legal gap contradicts the principles of legality and legal certainty, ultimately weakening victim protection. Structural factors such as poverty and non-inclusive policies including the abolition of sectoral minimum wages under the Omnibus Law on Job Creation further exacerbate the vulnerability of rural women to exploitation. Therefore, a comprehensive revision of the Anti-Trafficking Law is urgently needed, integrating the principles of human rights protection, non-discrimination, and legal harmonization through the adoption of the Palermo Protocol, the ratification of ILO Convention C190, and the strengthening of community empowerment and digital literacy. These efforts are expected to realize substantive justice and enhance the effectiveness of Indonesia’s criminal law in breaking the chain of technology-based female trafficking.